THE EFFECT OF TRAINING METHOD AND BALANCE ON SKILL OF WEIGHT LIFTHING SNATCH (The Experimental Study for Students at Faculty of Sport Science State University of Manado) - Lasut, Julien S.; Tangkudung, James A.P. (JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The experimental study is aimed to find out comparison of the effect of two training methods upon skills of snatch. The training method consists of both weight and plyometric training method. This research also aimed to find out interaction between training method and balance toward skill of snatch. The balance consists of both high and low balance. This research was carried out in Faculty of Sport Science, State University of Manado, in the academic year of 2012/2013. The experimental method using factorial design 2x2. The sample consisted of 40 students divided into four groups, each consisting of 10 students. The analyzing techniques of data were two-way analyses of variance (ANOVA) and further continued by Tukey test at Î±= .05 level significance. The result of this research shows that (1) in general, skill of snatch using weight training method is higher than those using plyometric training method, (2) for high balance using weight training method is higher than those plyometric training method, (3) for low balance using weight training and plyometric training method are not different at Î±= .05 level significance, (4) there is interaction between training method and balance toward skill of weight lifting snatch.